1990
DOI: 10.1143/jjap.29.2822
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Radical-Assisted Chemical Vapor Deposition of SiN Films Using Si(CH3)4 and NH2CH3

Abstract: Hydrogen radicals generated by microwave were employed in the growth of SiN films using tetramethylsilane and monomethylamine as source gases. Under appropriate experimental conditions, SiN film containing almost stoichiometrical nitrogen and small residual contents of carbon and oxygen was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This allowed us to predict the chemistry of the CVD process, which was determined by the reactivity of the source compound in the atomic hydrogen environment. It is noteworthy that remote hydrogen plasma chemical vapor deposition (RHP‐CVD) has been successfully used for the fabrication of a broad class of technologically important thin‐film materials, including silicon‐based films such as amorphous hydrogenated silicon (a‐Si:H),8–13 silicon carbide (a‐Si:C:H),5, 14–20 silicon nitride (a‐Si:N:H),21, 22 and silicon carbonitride (a‐Si:N:C:H)23 and metal‐based films such as Zn:S:Se,24 Ga:As,25 Cu,26 Ti:N,27 and Ta:N 28…”
Section: Introductionmentioning
confidence: 99%
“…This allowed us to predict the chemistry of the CVD process, which was determined by the reactivity of the source compound in the atomic hydrogen environment. It is noteworthy that remote hydrogen plasma chemical vapor deposition (RHP‐CVD) has been successfully used for the fabrication of a broad class of technologically important thin‐film materials, including silicon‐based films such as amorphous hydrogenated silicon (a‐Si:H),8–13 silicon carbide (a‐Si:C:H),5, 14–20 silicon nitride (a‐Si:N:H),21, 22 and silicon carbonitride (a‐Si:N:C:H)23 and metal‐based films such as Zn:S:Se,24 Ga:As,25 Cu,26 Ti:N,27 and Ta:N 28…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] This enables one to predict the chemistry of the CVD process, which is determined by the reactivity of the source compound with the hydrogen or oxygen radicals. The recent studies showed that RHP-CVD was successfully used for the fabrication of a broad class of thin- film materials comprising silicon-based films: amorphous hydrogenated silicon (a-Si:H), [10][11][12][13][14][15] silicon carbide (a-Si:C:H), 5, [16][17][18][19][20][21] silicon nitride (a-Si:N:H), [22][23][24] and metalbased films (Zn:S:Se, 25 Ga:As, 26 copper 27 ) whereas ROP-CVD was used for the production of a high-quality amorphous silica (a-SiO 2 ) films. [28][29][30][31] Although the structure and properties of the films produced by the remote plasma CVDs were studied extensively, knowledge of the chemistry involved in these processes is poor as yet.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the CVD process can be initiated in a homogeneous step, with an exclusive contribution of atomic hydrogen or atomic oxygen. This enables one to predict the chemistry of the CVD process, which is determined by the reactivity of the source compound with the hydrogen or oxygen radicals. The recent studies showed that RHP−CVD was successfully used for the fabrication of a broad class of thin- film materials comprising silicon-based films: amorphous hydrogenated silicon (a-Si:H), silicon carbide (a-Si:C:H), , silicon nitride (a-Si:N:H), and metal-based films (Zn:S:Se, Ga:As, copper) whereas ROP−CVD was used for the production of a high-quality amorphous silica (a-SiO 2 ) films. Although the structure and properties of the films produced by the remote plasma CVDs were studied extensively, knowledge of the chemistry involved in these processes is poor as yet. Therefore, we have undertaken a mechanistic study related to the formation of two technologically important thin-film materials, namely, a-Si:C:H and a-SiO 2 , which in the present work are produced from hexamethyldisilane (HMDS) and trimethylsilane (TrMS) by RHP−CVD and from tetraethoxysilane (TEOS) by ROP−CVD, respectively.…”
Section: Introductionmentioning
confidence: 99%